[tex]\lim_{x\to\0}\frac{98}{83} (\frac{1-cos3x.cos5x.cos7x}{sin^2 7x})[/tex])
Ta có
1 - cos3xcos5xcox7x = 1 -[TEX] \frac{1}{2}[/TEX].(cos8x + cos 2x)
= 1 - [TEX]\frac{1}{2}[/TEX].(cos8xcos7x + cos2x.cox7x)
= 1 - [TEX]\frac{1}{4}[/TEX].(cos15x + coxx + cos9x + cos5x )
= [TEX]\frac{1}{4}[/TEX](4 - cos15x - cosx - cos9x - cos5x)
= [TEX]\frac{1}{4}[/TEX][( 1 - cos15x) + (1 - cosx) +( 1 - cos9x)
+( 1- cos5x)
= [TEX]\frac{1}{4}[/TEX]([TEX]2sin^2 \frac{15x}{2}[/TEX]+[TEX]2sin^2 \frac{x}{2}[/TEX]+]([TEX]2sin^2 \frac{9x}{2}[/TEX]+]([TEX]2sin^2 \frac{5x}{2}[/TEX]
= [TEX]\frac{1}{2}[/TEX]([TEX]2sin^2\frac{15x}{2}[/TEX] + [TEX]2sin^2\frac{x}{2}[/TEX] + [TEX]2sin^2\frac{9x}{2}[/TEX] + [TEX]2sin^2\frac{5x}{2}[/TEX]
Do đó :
[TEX]lim_x->\infty[/TEX][TEX]\frac{98}{83}[/TEX][TEX]\frac{1 - cos3xcos5xcos7x}{sin^27x}[/TEX]
= [TEX]lim_x->\infty[/TEX][TEX]\frac{1}{2}[/TEX]([TEX]sin^2\frac{15x}{2}[/TEX]+[TEX]sin^2\frac{x}{2}[/TEX] + [TEX]sin^2\frac{9x}{2}[/TEX] + [TEX]sin^2\frac{5x}{2}[/TEX]
=[TEX]\frac{98}{83}[/TEX].[TEX]\frac{1}{2}[/TEX].l[TEX]lim_x->0[/TEX][TEX]\frac{sin^215x/2}{(15x/2)^2}[/TEX].[TEX](\frac{15x}{2})^2[/TEX]+[TEX]\frac{sin^2x/2}{(x/2)^2}[/TEX].[TEX](\frac{x}{2})^2[/TEX]+[TEX]\frac{sin^29x/2}{(9x/2)^2}[/TEX].[TEX](\frac{9x}{2})^2[/TEX]+[TEX]\frac{sin^25x/2}{(5x/2)^2}[/TEX].[TEX](\frac{5x}{2})^2[/TEX].[TEX]\frac{(7x)^2}{sin^27x}[/TEX][TEX]\frac{1}{(7x)^2}[/TEX](=1)
=[TEX]\frac{98}{83}[/TEX].[TEX]\frac{1}{2}[/TEX][TEX]lim_x->0[/TEX]( ([TEX](\frac{15}{2})^2[/TEX] +( [TEX](\frac{1}{2})^2[/TEX]) + ([TEX](\frac{9}{2})^2[/TEX]) + ([TEX](\frac{5}{2})^2[/TEX])) .[TEX]\frac{1}{(7)^2}[/TEX]
= 1
-----------
%%-%%-%%-%%-%%-%%-%%-%%-